2020
DOI: 10.1002/jocb.483
|View full text |Cite
|
Sign up to set email alerts
|

Is There Really a Creativity Crisis? A Critical Review and Meta‐analytic Re‐Appraisal

Abstract: The idea of a "creativity crisis" is widely accepted in the creativity and education literature. Its popular interpretation as a decline in creativity across generations originates from Kim's (2011) influential analysis of the re-norming data in the Torrance Tests of Creative Thinking (TTCT). The present work offers a critical review and reappraises the findings of Kim ( 2011), while incorporating new data from the latest norming edition of the TTCT. We posit that Kim's (2011) claim of creativity decline was g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Compared with other previously studied correlates of CA, such as openness to experience and creative self-efficacy (e.g., da Costa et al, 2015; Haase et al, 2018; Karwowski & Lebuda, 2016), it seems that CA may be poorly predicted by DT. In sum, our results may be interpreted as support for the notion that reliance on DT tests as the sole indicator of creativity may be inappropriate and misleading (Barbot & Said-Metwaly, 2021; Hocevar, 1980; Runco & Acar, 2012). Having high creative potential does not equate to enacting this potential into real-life achievements.…”
Section: Discussionsupporting
confidence: 73%
“…Compared with other previously studied correlates of CA, such as openness to experience and creative self-efficacy (e.g., da Costa et al, 2015; Haase et al, 2018; Karwowski & Lebuda, 2016), it seems that CA may be poorly predicted by DT. In sum, our results may be interpreted as support for the notion that reliance on DT tests as the sole indicator of creativity may be inappropriate and misleading (Barbot & Said-Metwaly, 2021; Hocevar, 1980; Runco & Acar, 2012). Having high creative potential does not equate to enacting this potential into real-life achievements.…”
Section: Discussionsupporting
confidence: 73%
“…Yet are we really in crisis? Importantly and fortunately, there is no evidence for that (Barbot & Said-Metwaly, 2021).…”
mentioning
confidence: 99%
“…When re-analyzing the data of Kim (2011), by considering updated normative values from the last Torrance Test of Creativity Thinking (TTCT-Figural), Barbot and Said-Metwaly (2020) concluded that the notion of creativity decline was grounded on problematic empirical decisions, statistical approaches, data representation, TABLE 1.…”
Section: Creativity Developmentmentioning
confidence: 99%
“…When re‐analyzing the data of Kim (2011), by considering updated normative values from the last Torrance Test of Creativity Thinking (TTCT‐Figural), Barbot and Said‐Metwaly (2020) concluded that the notion of creativity decline was grounded on problematic empirical decisions, statistical approaches, data representation, and interpretation of findings. This seems to show that the operationalization of a “creativity crisis” is based on a rather narrow operationalization of the phenomenon and raises issues about the conceptualization and the measurement of creativity, which might need to be expanded beyond the “golden standard” of using the TTCT for creativity measurement (Barbot & Said‐Metwaly, 2020). However, research has shown that creativity is a skill that can be trained, with interventions presenting encouraging levels of effectiveness (Birdi, 2016; Ma, 2009; Mansfield, Busse, & Krepelka, 1978; Rose & Lin, 1984; Scott et al., 2004a).…”
Section: Creativity Landscapesmentioning
confidence: 99%
See 1 more Smart Citation